Pengaruh Video Animasi Berbasis Alat Peraga Edukasi Terhadap Hasil Belajar Siswa Pada Pembelajaran Matermatika di Kelas IV SD - Toriyanda, Toriyanda; Selegi, Susanti Faipri; Tanzimah, Tanzimah (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to determine the effect of animated video educational teaching aids on student learning outcomes in fourth grade Mathematics learning at SD Negeri 141 Palembang. This research is a quantitative type using the True Experimental Design experimental research method with a Posttest-Only Control Design. The population of this study were all fourth-grade students at SD Negeri 141 Palembang. The sample for this research was class IV students. A and IV. B with a total of 59 students. The sample selection technique used was census or total sampling. Data collection techniques in this research are tests and documentation. Data analysis used the Independent Sample T-test. The results of this research show that the average posttest learning outcome score for the experimental class is 77.24 and the control class is 71.20. The results of the t-test calculation of learning outcomes obtained t_count = 2.226 > t_table = 1.67203 with a significance level = 0.05. Based on the research results, it can be concluded that there is a significant influence of the use of animated video teaching aids on student learning outcomes in class IV Mathematics learning at SD Negeri 141 Palembang.